Exploring Verbal Linguistic Intelligence, Writing Self-Efficacy, and Writing Skills Among Undergraduate Students - Nafisa, Naela Ainun; Putro, Nur Hidayanto Pancoro Setyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to investigate relationship between verbal linguistic intelligence, writing self-efficacy, and writing skills. This research adopted correlational quantitative design for second semester of English department in Unissula. Data were collected through tests for obtaining data of verbal linguistic intelligence and writing skills, then using questionnaires for obtaining data of writing self-efficacy. The results of this research are as follow: 1) Verbal linguistic intelligence has a significant relationship to writing skills. 2) The relationship between writing self-efficacy which has several dimensions such as ideation, conventions, and self-regulation does not have a significant correlation with writing skills. 3) The relationship among verbal linguistic intelligence, writing self-efficacy, and writing skills can be seen from the direct influence and indirect influence. These findings underscore that verbal linguistic intelligence is a key factor in improving writing skills, while writing self-efficacy may have limited role